Membentuk Karakter Enterperneurship Untuk Mahasiswa Dalam Mata Kuliah Kewirausahaan - Khurin’In Ratnasari (Entrepreneurship Faculty, Universitas Garut, 2019)
The unemployment rate in Indonesia continues to increase. This is one of the main problems of economic development in Indonesia. According to BPS data, in November 2017, the unemployment rate in Indonesia reached 5.50% while economic growth in the third quarter of the same year was 5.03%, an increase from 4.79% in 2014 which is the lowest growth in the last six years. Higher education institutions (HEIs) play an important role in building national characters including the entrepreneurship character, which can be an answer to the question of unemployment. In this respect, HEIs are expected to contribute to bring about productive and innovative entrepreneurs who can seize opportunities in various fields such as agriculture, fishery, industry, farming, and services.